2009
DOI: 10.1039/b905130a
|View full text |Cite
|
Sign up to set email alerts
|

A novel route to polymeric sub-micron fibers and their use as templates for inorganic structures

Abstract: A simple and generic method is described to prepare polymeric sub-micron fibers by freeze drying dilute polymer solutions; these polymeric fibers are then used as templates to fabricate inorganic structures via a sol-gel process or ion crosslinking reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…94,95 Very recently, it was found that diluted aqueous polymer solutions could be frozen in liquid nitrogen and then freeze dried to produce polymeric nanofibres with diameters in the range of 200-600 nm. 96 A range of hydrophilic nanofibres including PVA, SCMC and alginate were successfully obtained. The polymeric nanofibres could then be used as templates to prepare hollow crystalline titania microtubes and Fe 2 O 3 nanofibres.…”
Section: Microwires and Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…94,95 Very recently, it was found that diluted aqueous polymer solutions could be frozen in liquid nitrogen and then freeze dried to produce polymeric nanofibres with diameters in the range of 200-600 nm. 96 A range of hydrophilic nanofibres including PVA, SCMC and alginate were successfully obtained. The polymeric nanofibres could then be used as templates to prepare hollow crystalline titania microtubes and Fe 2 O 3 nanofibres.…”
Section: Microwires and Nanowiresmentioning
confidence: 99%
“…Figure 9 shows the SEM images of SCMC nanofibres and hollow TiO 2 microtubes. 96 Chitosan and chitosanbased fibres with diameter from 100-700 nm were also produced by freeze drying 0.1 wt% solutions. 97 This method overcame some disadvantages of the electrospinning methods such as the requirement for toxic organic solvents or highly concentrated acetic acid as the solvent.…”
Section: Microwires and Nanowiresmentioning
confidence: 99%
“…Recently, sub-micron polymer fibres and inorganic structures were prepared by freeze drying dilute aqueous polymer solutions (Qian et al 2009). The fibres could be used as scaffolds with a high surface area and easy accessibility for a range of applications.…”
Section: (C) Silica Spheres On Sub-micron Fibresmentioning
confidence: 99%
“…The SCMC fibres were cross-linked with FeCl 3 before use (Qian et al 2009). Chitosan and Fe-SCMC composite fibres were added into the reaction system instead of polyHIPE beads as described above.…”
Section: (C) Stöber Synthesis In the Presence Of Nanofibresmentioning
confidence: 99%
See 1 more Smart Citation